La place du paysagiste dans le paysage agricole - Laurence Renard (Projets de Paysage)
Whereas a similarity between landscape architects and farmers had been clearly established in the 1990s, the aesthetic approach to the landscape is sometimes criticised by the farming sector which defends its vocation of producing food. Giving lessons about the landscape therefore becomes counter-productive. There is a strong temptation to assume the responsibility of the landscape by becoming a farmer-cum-landscape architect. Or then it is the landscape architect who changes posture. Through two projects, one in the Beauce region and the other in Brittany, this new posture has been experimented with. These two experiments raise the question of the legitimacy of the landscape architect in taking a position regarding the agricultural landscape and deciding about its future. They challenge usual procedures and modes of governance. The results of these experiments are convincing but what are the consequences for the profession and for the training and aspirations of landscape architects? What is the profile of the “new landscape architect” which emerges from these questions?